Somalia: Ageing Situation and the Demand for Geriatric Care - BakiBillah, Abul Hasan; Muhammad, Faisal; Ali Haidari , Basit; Rummana, Shahrukh (Health Nexus, 2025)
Due to the aftermath of decades of strikes, conflicts, and wars, Somalia's health care institutions have become fragile and crippled. Today's adult population is going to get into the elderly group. Evidence suggests that elderly people have special health care needs, including chronic care. On that ground, it is imperative to start working to strengthen the crippled health care delivery system of Somalia for meeting the demand for elderly care.